Pengaruh pengembangan sumber daya manusia dan kemampuan kerja terhadap kinerja karyawan PT. Jambi Media Grafika â€œTribun Jambiâ€ - Adela Pramesrianto; Edward Edward; Shofia Amin (Jurnal Dinamika Manajemen, 2020)
This study aimed to determine whether the development of human resources and workability affects employee performance. The data used in this study are primary data obtained through interviews, questionnaires and processed with the help of SPSS 22 and Windows 10. The population in this study were all employees at PT. Jambi Media Grafika or Tribun Jambi and the sample amounted to 60 people. Research from the hypothesis proves that workability has a positive and significant effect on employee performance, but workability has no significant impact. This research implies that human resource development improves and enhances employee performance.